Uma análise dos determinantes do sucesso do candidato ao legislativo no Estado do Ceará: uma análise comparativa em três níveis de governo - Pimentel, João Paiva Matos (2015)
This article investigates the determinants of the probability of candidates to the legislature election in the state of Ceará. Variables such as the transfer of donated resources and costs, and socioeconomic characteristics of the candidates are also incorporated into models of binary dependent variables where the dependent variables represent the electoral success for federal deputies, state representatives and councilors of Fortaleza and Caucaia. The results allow us to infer that the ability to raise revenue for the election campaign is a decisive factor for the candidates for the legislative election in the state of Ceará. The findings also suggest that the political influence of parliamentarians already arises in the period of the electoral process, even in the condition of candidates, who collect funds for their campaigns. Moreover, it evidences that the spending efficiency campaign is also a key factor for success, although reducing its effects as the political importance of the position decreases.